Topical administration of Tamanu Oil (Calophyllum inophyllum) inhibited the increase of matrix metalloproteinase-1 (MMP-1) expressions and decrease of collagen dermis amount in male wistar rats exposed to ultraviolet B - Yoselyn Gunawan; Alex Pangkahila; Agus Eka Darwinata (Neurologico Spinale Medico Chirurgico, 2021)
Background: UV-B irradiation is the major causative factor in photoaging. Photoaging increases MMP-1 significantly and cause damage to collagen by forming ROS. The monounsaturated free fatty acids and antioxidant compounds in Tamanu oil have been studied to inhibit the emergence of MMP-1 and maintain collagen amount. The study aimed to investigate topical Tamanu oil in inhibiting MMP-1 expressions and collagen decrease in male Wistar rats’ skin exposed to UV-B. Methods: A randomized post-test-only control group design was performed on 36 male Wistar rats, aged 2-3 months old with 180-220 grams body weight. They were assigned to two groups: the placebo group and the Tamanu oil group. Both groups were given the same amount of UV-B exposure for four weeks totalling in 840 mJ/cm2 of dosage radiation. Their dermis was examined for MMP-1 using Immunohistochemistry and collagen amount using Picro Sirius Red staining. Results: A comparative analysis was done to show the difference between groups. The mean expression of MMP-1 in the control group was 34,03±2.97 cell/HPF and the Tamanu oil group was lower at 22.73±2.68 cell/HPF. The mean amount of collagen dermis in the control group was 38.90±11.64 % and the Tamanu oil group was higher at 65.66±8.13 %. A significant difference was shown in the two groups (p<0.05). Conclusion: Topical Tamanu oil has proven to hinder the increase of MMP-1 expressions and collagen amount in male Wistar rats’ skin exposed to UV-B.